1) Ta có:
[TEX]a-b=2a+2b[/TEX]
[TEX]\Rightarrow a=-3b[/TEX] (1)
Lại có:
[TEX]a-b=\frac{a}{b}[/TEX] (2)
Thay (1) vào (2) ta được:
[TEX] -3b-b=\frac{-3b}{b}[/TEX]
[TEX]\Rightarrow -4b=-3[/TEX]
[TEX]\Rightarrow b=\frac{3}{4}[/TEX]
Lại có: [TEX]a=-3b[/TEX]
[TEX]\Rightarrow a=\frac{-9}{4}[/TEX]
2)Ta có:
[TEX]a+b=ab[/TEX]
[TEX]\Rightarrow a=ab-b=b(a-1)[/TEX]
[TEX]\Rightarrow \frac{a}{b} = a - 1[/TEX]
Lại có:
[TEX]\frac{a}{b} = a+b[/TEX]
[TEX]\Rightarrow a-1=a+b[/TEX]
[TEX]\Rightarrow a-1-a = b[/TEX]
[TEX]\Rightarrow b= -1[/TEX]
Do [TEX]a+b=ab[/TEX]
[TEX]a+(-1)= a.(-1)= -a[/TEX]
[TEX]a+a = 1 \Rightarrow 2a=1[/TEX]
[TEX]\Rightarrow a = \frac{1}{2}[/TEX]
3) Ta có:
[TEX]x+\frac{1}{x}= \frac{x^2+1}{x}[/TEX]
Để [TEX]\frac{x^2+1}{x}[/TEX] là số nguyên [TEX]\Rightarrow x^2+1[/TEX] phải chia hết cho x
Lại có [TEX]x^2[/TEX] chia hết cho x
[TEX]\Rightarrow x^2+1-x^2[/TEX] chia hết cho x
[TEX]\Rightarrow 1[/TEX] chia hết cho x
[TEX]\Rightarrow x=1[/TEX] hoặc [TEX]x=-1[/TEX]